Hubungan Riwayat Atopi dengan Kejadian Dermatitis Kontak Akibat Kerja Pekerja Batik di Denpasar Barat - Efrilia; Sayu Widiawati; Luh Gede Pradnyawati (Aesculapius Medical Journal, 2024)
[The Correlation Between The History of Atopy with The Incidence of Occupational Contact Dermatitis on Batik Workers in West Denpasar] The skin is the largest and most comprehensive organ that protects the body from exposure to diseases from outside the body. Occupational contact dermatitis (OCD) is a condition of skin disorders caused by substances or processes in the work environment. A history of atopy is a hypersensitivity reaction due to exposure to foreign objects in the environment that tends to be inherited or genetic. This study aims to determine the relationship between atopy history and the incidence of occupational contact dermatitis in batik workers in the West Denpasar sub-district. The research design was analytically observational with a cross-sectional approach conducted in 19 batik industries in the West Denpasar sub-district in June 2021. The number of research samples obtained was 108 people using consecutive sampling techniques. Data was collected by filling out a questionnaire through interviews. The results showed that 29 people (26.9%) experiencing OCD and 61 (56.5%) had a history of atopy. Based on this data, for batik workers who have a history of atopy, 21 people (17.0%) experience OCD, and 40 people (83.0%) do not experience OCD. In batik workers who do not have a history of atopy, 8 people (34.3%) experience OCD, and 39 workers (65.6%) do not experience OCD. The results of the bivariate analysis showed that there was a significant relationship between atopy history and the incidence of occupational contact dermatitis in batik workers in the West Denpasar sub-district (p-value = 0.043; PR = 2.023; 95% CI = 1.014-6.461). The conclusion is that there is a significant relationship between the history of atopy and the incidence of occupational contact dermatitis in batik workers in the West Denpasar sub-district.